Data Mining and Social Media Analysis to Identify Key Dimension of Service Quality for BTN Mobile App in Indonesia - Aris, Valentino; Ashdaq, Muhammad; Taufik, Muhammad (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to analyse the online service quality in Indonesia's banking sector. We will carry out a consumer sentiment analysis on the BTN Mobile application, which Bank Tabungan Negara (BTN) uses to provide online services to consumers. Data mining will be done to obtain consumer review data on the Google Play Store. The target amount of data is a maximum of 500 data. The data will then be analysed to produce word clouds, topic modelling, and consumer sentiment and to produce dimensions that influence service quality. Analysis was carried out using the Orange Data Mining Application. The analysis results show dimensions that receive positive, negative and neutral sentiment from BTN Mobile users in Indonesia.